Temperature-induced reversible micelle–vesicle transition in aqueous solution of a pseudogemini surfactant without any additive. Issue 42 (17th May 2017) - Liu, Xuemin; Wang, Jingwen; Cui, Zhenggang; Yao, Heping; Ge, Xin; Chen, Wen; Sun, Fengli
Abstract : Temperature-induced reversible micelle–vesicle transition is achieved in aqueous solution of a single pseudogemini surfactant without any additive. Abstract : Temperature-induced reversible micelle–vesicle transition is achieved in aqueous solution of a single pseudogemini surfactant without any additive. The pseudogemini surfactant is constructed by tetradecyldimethylamine (DA14) and maleic acid (MA) at a 2 : 1 molar ratio of DA14/MA in aqueous solution via non-covalent bonds. The transition temperature can be adjusted by changing either the total surfactant concentration or the DA14/MA ratio. This reversible system, which has both low material costs and convenience, has potential applications in household and industry fields.